2010
DOI: 10.1111/j.1365-2672.2010.04761.x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of buttermilk for fermentation with Lactobacillus helveticus and production of a functional peptide-enriched powder by spray-drying

Abstract: Aim:  To ferment buttermilk, a low‐cost by‐product of the manufacture of butter, with a proteolytic strain of Lactobacillus helveticus, to enhance its value by the production of a functional peptide‐enriched powder. Methods and Results:  Buttermilk was fermented with Lact. helveticus 209, a strain chosen for its high proteolytic activity. To enhance the release of peptidic fractions, during fermentation pH was kept at 6 by using NaOH, Ca(CO)3 or Ca(OH)2. Cell‐free supernatant was recovered by centrifugation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
4
26
0
2
Order By: Relevance
“…), however, certain characteristics of probiotics in general (sensitivity to lactic acidity or osmotic pressure, need of low storage temperature) have confined them mainly to dairy products (yoghurt, cheese), limiting the development of other kinds of food products (Burns et al . ; Peteán et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), however, certain characteristics of probiotics in general (sensitivity to lactic acidity or osmotic pressure, need of low storage temperature) have confined them mainly to dairy products (yoghurt, cheese), limiting the development of other kinds of food products (Burns et al . ; Peteán et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work (Burns et al . ), it was observed that pH control of the fermentation using NaOH dramatically increased the content of sodium in the final product. The product under study will be used, once optimised, for the development of new functional foods.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, it was observed that pH controlled buttermilk fermentation led to an increase in the salt content (as Na and Ca lactate) of the fermentation medium (Burns et al . ), which led to an increase of the osmotic pressure. Lactic acid bacteria display acid resistance mechanisms to survive the by‐products of their own metabolism (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations